The Formin DAAM Functions as Molecular Effector of the Planar Cell Polarity Pathway during Axonal Development in Drosophila. - Gombos, R.; Migh, E.; Antal, O.; Mukherjee, A.; Jenny, A.; Mihály, J. (Journal of Neuroscience, 2015)
Recent studies established that the planar cell polarity (PCP) pathway is critical for various aspects of nervous system development and function, including axonal guidance. Although it seems clear that PCP signaling regulates actin dynamics, the mechanisms through which this occurs remain elusive. Here, we establish a functional link between the PCP system and one specific actin regulator, the formin DAAM, which has previously been shown to be required for embryonic axonal morphogenesis and filopodia formation in the growth cone. We show that dDAAM also plays a pivotal role during axonal growth and guidance in the adult Drosophila mushroom body, a brain center for learning and memory. By using a combination of genetic and biochemical assays, we demonstrate that Wnt5 and the PCP signaling proteins Frizzled, Strabismus, and Dishevelled act in concert with the small GTPase Rac1 to activate the actin assembly functions of dDAAM essential for correct targeting of mushroom body axons. Collectively, these data suggest that dDAAM is used as a major molecular effector of the PCP guidance pathway. By uncovering a signaling system from the Wnt5 guidance cue to an actin assembly factor, we propose that the Wnt5/PCP navigation system is linked by dDAAM to the regulation of the growth cone actin cytoskeleton, and thereby growth cone behavior, in a direct way.